Babies at random - VICTORIA JARDON, ANA MARIA (Advances in Social Sciences Research Journal, 2016)
The present study was conducted about the causes of unwanted adolescent pregnancy. The analysis was on pregnant and not pregnant adolescents; was comparatively analysed the circumstances, family situation, self-esteem, life goals and school notes, knowledge on sexual education, attitudes, situation of family integration, dynamic related to pregnancy and its situation later, relationship with the father of the baby. The research was conducted in three stages. The main results were: the pregnant adolescents among the stages show low self-esteem, low school notes, without life goals. They informed their parents at 22 weeks, the 56% abandoned the school, and 90%were abandoned by the father of the baby. In preteens from 10 to 11 years of age, about the sexual information, the source of this information and differences by gender of this education. Boys are significantly more informed than girls; boys received information from fathers, mothers and other members of the family. The girls received information from Internet and adult conversations. 22% of the preteens has adolescent’s family members with unwanted pregnancy.